Adakah Pengaruh E-WoM, Brand Awareness, Brand Image Terhadap Keputusan Pembelian Codac? - Iskandar, Olivia Mey; Dewi, Liliana (Universitas Katolik Darma Cendika, 2025)
The development of the fashion industry in Indonesia has experienced significant growth alongside modernization and technological advancements. One trend that has become the center of attention is the popularity of oversized t-shirts, including brands like CODAC products online. This research aims to examine the influence of electronic word of mouth (e-WoM), brand awareness, and brand image on the decision to purchase CODAC products online using WhatsApp and Line. The research method used is quantitative with a cross-sectional research design. The sampling technique employed is nonprobability sampling with purposive sampling by distributing questionnaires to CODAC product customers. The sample used in this study consists of 62 respondents. The sample criteria determined are CODAC customers who have previously made transactions, aged 17 to 30 years old in the Surabaya area. The questionnaire tabulation results were then processed using multiple linear regression analysis with SPSS version 25. The results of this study indicate that e-Word of Mouth (e-WoM), brand awareness, and brand image have a positive and significant impact on the decision to purchase CODAC products online through WhatsApp and Line among the people of Surabaya. Subsequent testing indicates that all independent variables collectively influence the purchase decision by 96.8%.